Pendampingan Penguatan Kompetensi Guru dan Siswa SMA Melalui Pengembangan Inovasi Sains dan Kompetisi Olimpiade Biologi di Kabupaten Sampang, Madura - Eko Suyanto; Anna Safitri; Nia Kurnianingsih; Fatchiyah Fatchiyah (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2020)
Teachers and students need more knowledge to improve their competence. The educational quality can be improved by varying learning methods and supported by competition. This community service activity aims to strengthen the competence of teachers and students through learning innovation in the Biology subject and to provide learning competition of Biology Olympiad through simulation and training. The community-based research (CBR) method was performed by workshop and training involving 60 participants. As many as 100% of the participants attended the activities. The results indicated that the participants acquired new knowledge and realized their competence skills. Learning innovation and competition were able to improve their knowledge and competence. The participants are eager to apply the methods learned at school. These new competence and skill are expected to improve the quality of education